Resilience Theory: Risk and Protective Factors for Novice Special Education Teachers - Benjamin, Thomas L.; Black, Rhonda S. (Journal of the American Academy of Special Education Professionals, 2012)
This study describes experiences of novice special education teachers in rural areas in Hawaii through a lens of resiliency theory. Two types of support--administrative and collegial--were examined in terms of being risk or protective processes. A case study design was used to give voice to five participants who expressed their satisfaction and concerns about support from administrators, interactions, expectations, recognition, teaching assignments, meetings and time. The study also examined support from general and special education colleagues, school staff, and outside service providers. Research findings may be of value to local, district, and state administrators and university personnel who wrestle with the issues of recruitment, preparation, and retention of special education teachers.